Information Literacy as a Situated Practice in the Neoliberal University - Nicholson, Karen (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
Information literacy (IL) emerges within the context of a neoliberal agenda in higher education. This paper uses the Academic Literacies Framework (Lea and Street, 1998, 2006) to critique current LIS approaches to IL, and to reframe IL as a situated practice within the neoliberal university. La compétence informationnelle s’impose comme une priorité de tout programme néo-libéral dans l'enseignement supérieur. Cet article s’appuie sur l’Academic Literacies Framework (Lea and Street, 1998, 2006) pour soumettre à la critique les approches actuelles de la compétence informationnelle dans les sciences de l’information et la bibliothéconomie, et la recadrer comme pratique d’immersion dans l'université néo-libérale. *** Awarded Best Paper by a Practitioner ***